Influence of Parent’s Behavior to the Children Awareness on the Environmental Preservation - Indriyani Rachman; Matsumoto Toru; Yonik Meilawati Yustiani (Lembaga Penelitian Universitas Pasundan, 2015)
The environmental conditions in Indonesia, especially those in the urban areas, have experienced very severe quality degradation. From the aspect of culture, the Indonesia people have inherited customs and traditions on preservation of their nature and environment. Tradition and cultures including values are usually transferred from parents to their children. In this research, a survey was conducted to investigate the influence of parents’ behavior on the children knowledge on the environmental preservation awareness. Respondents were selected from several elementary school students located near Cikapundung River, Bandung-Indonesia. Questionnaires were distributed to explore on how the students preserve the river located near their school. The research showed that the behavior ofthe parents had a weak positive correlation to the knowledge of the child in maintaining the environment, with the determination coefficient of 0.3. Local traditions or wisdom which tend to appreciate nature and environment have also been faded. As much as 46 percent of respondent believe that wastewater can be discharged directly to the river. This research result also conclude that not only the children’s environmental awareness that need to be increased, but their parents’ through official environmental education at school and upholding the local wisdoms in the community. With the involvement of other key stakeholders, the environmental education and the preservation of the local wisdom then can be maintained in the future. Keywords: parents’ behavior, children awareness of environmental preservation